Radiotherapy in Leptomeningeal Disease: A Systematic Review of Randomized and Non-randomized Trials - Buszek, Samantha M.; Chung, Caroline (Frontiers in Oncology, 2019)
Background: Leptomeningeal disease (LMD), also known as neoplastic meningitis, leptomeningeal carcinomatosis, or carcinomatous meningitis, is a rare cancer complication occurring in approximately 5% of cases and ultimately leads to significant morbidity and mortality. In the modern era, incidence of this condition continues to rise with longer survival of patients with advanced and even metastatic disease due to continued improvements in systemic therapies that are providing prolonged control of distant disease, but with limited effect in the central nervous system (CNS). Typical treatment strategies include optimal systemic therapy for the primary disease, as well as neuroaxis directed therapies, which may include intrathecal chemotherapy (ITC) or radiotherapy (RT). Methods: A systematic review of radiotherapy for LMD was performed. Medline, EMBASE, and Cochrane databases were searched from 1946-2018 for clinical trials, retrospective/prospective reviews, and case series with ≥2 human subjects that used radiation therapy techniques in the treatment of LMD. The outcome measures of interest included: characteristics of trial participants, inclusion/exclusion criteria, study type, number of participants, primary cancer histology, type of intervention for LMD, survival results if reported, length of follow up, and study conclusion. Results: Of 547 unique citations, 62 studies met the pre-specified eligibility criteria. These studies included 36 retrospective cohorts, 11 prospective series, 12 case series, and a single citation of guidelines, NCDB analysis, and a randomized control trial. Owing to study heterogeneity, meta-analyses of the endpoint data could not be performed. Conclusions: LMD is a devastating complication of cancer with reported survivals ranging from 2-4 months. Based on this systematic review, the recommendation for the treatment of LMD is for multimodality discussion of cases and treatment, including the use of radiotherapy, for LMD. However, with continued advances in systemic therapy as well as imaging advances, the landscape of LMD is evolving rapidly and the role of RT will likely also continue to evolve and advance. There is limited high-quality evidence to guide the optimal use of RT for the treatment of LMD, and there is a great need for prospective, histology specific investigation of the role of radiotherapy for LMD in the era of modern systemic therapies.